Afetividade e sexualidade de jovens em situação de deficiência na Educação Básica - Batista, Geisa Cristina (2022)
Affectivity and sexuality are presented as central dimensions of human beings, which include: their relationship with their bodies and with the bodies of others, emotional bonds, questions about love, sexual intimacy, gender identity, sexual orientation and human reproduction. People with disabilities have access rights to information and knowledge constructions in these areas. This research, with a qualitative approach, aimed to describe the perception that young people with disabilities, enrolled in Basic Education, have about affectivity and sexuality. Eleven young people gave semi-structured interviews between 2020 and 2021. Textual Discursive Analysis was adopted to analyze and interpret the data. The results showed the public school as the common space for the initial development of affective-sexual relationships, and more effectively when it was located in the same residential neighborhood, due to the dynamics in social interactions, in external leisure social events. The few opportunities to access art, sports activities and social events outside the school were factors considered to hinder the development of affective-sexual relationships with peers. This is worrying data, as it makes the achievement of autonomy in the experiences of young people unfeasible. Male latex condoms and non-completion of the sexual act were the knowledge measured against sexually transmitted infections, HIV and unwanted pregnancy, although they did not demonstrate experiences with proper use. Surveillance in the residential space, in friendships and in speeches to delay the beginning of affective-sexual relationships have been shown to cause fear, insecurity, guilt and conceptions about sexual acts related to the badness of other people in relation to their bodies, making it impossible to think about body touch , caresses and sex as something that should be pleasurable. It was detected: a) incidence of sexual violence with participants and with their acquaintances, whose perpetrators were men known from the family and school environment; b) lack of knowledge about social movements that fight against gender inequalities and prejudices; c) despite family prohibitions, both affective and sexual experiences were being carried out according to individual possibilities, in possible contexts and spaces; and d) absence of school education in affectivity and sexuality. It is considered that a more supportive, less violent society is built, sexually speaking, when education in affectivity and sexuality is provided, as well as access to art and sports activities that provide well-being and pleasure, as a way of developing a healthy youth physically and psychologically. It is thought that the viability of this adequate training allows for more assertive awareness and attitudes. Research is suggested on transgenerational sexual violence, in childhood and adolescence, with the aim of finding out whether it was perceived as initiation to sexual pleasures or sexual violence. Academic learning and the use of assistive technologies in Basic Education can also be the subject of future investigations.